2012
DOI: 10.1177/0271121412463086
|View full text |Cite
|
Sign up to set email alerts
|

Service Coordinators’ Perceptions of Autism-Specific Screening and Referral Practices in Early Intervention

Abstract: Service coordinators in a statewide early intervention program were surveyed to develop an understanding of screening and referral practices to identify children on the autism spectrum. Quantitative and qualitative data summarizing autismspecific screening and referral practices are reported. More than 50% of the respondents reported that they had never received a referral from a physician or another early intervention provider because a child has failed an autism-specific screening. While service coordinators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Qualitative Component.-Brief surveys and an in-person semi-structured qualitative interview protocols were developed by trained qualitative researchers for both EI providers and parents; interview guide domains and measures were informed by those published in the peer-reviewed literature and an inter-disciplinary research team. First, the EI provider survey and interview guide consisted of 40 categorical and open-ended questions that characterized respondents' (1) sociodemographic characteristics (Stahmer, 2007;Stahmer, Collings & Palinkas, 2005), (2) experiences providing EI services (Stahmer, 2007;Stahmer, Collings & Palinkas, 2005), (3) experiences administering ASD screening tools specifically, and perceptions of ASD (Pizur-Barnekow et al, 2013;Pizur-Barnekow Schefkind, 2014). Reported in this paper, EI providers were asked to describe the multi-stage screening process, and follow-up questions included specific probes about strategies they used when they and/or the parent lacked concern of ASD and rationale for these actions.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Qualitative Component.-Brief surveys and an in-person semi-structured qualitative interview protocols were developed by trained qualitative researchers for both EI providers and parents; interview guide domains and measures were informed by those published in the peer-reviewed literature and an inter-disciplinary research team. First, the EI provider survey and interview guide consisted of 40 categorical and open-ended questions that characterized respondents' (1) sociodemographic characteristics (Stahmer, 2007;Stahmer, Collings & Palinkas, 2005), (2) experiences providing EI services (Stahmer, 2007;Stahmer, Collings & Palinkas, 2005), (3) experiences administering ASD screening tools specifically, and perceptions of ASD (Pizur-Barnekow et al, 2013;Pizur-Barnekow Schefkind, 2014). Reported in this paper, EI providers were asked to describe the multi-stage screening process, and follow-up questions included specific probes about strategies they used when they and/or the parent lacked concern of ASD and rationale for these actions.…”
Section: Study Proceduresmentioning
confidence: 99%
“…While service coordinators working in EI report that EI providers have a role in conducting ASD-specific screening, more than 50% of the coordinators indicated that it would be difficult to complete ASD-specific screening in EI settings because of provider time constraints or lack of expertise and training (Tomlin et al, 2013). To address this concern, Pizur-Barnekow et al (2013) proposed that one member of an EI team could be trained in conducting and interpreting the results of an ASD-specific screening. Although it may be helpful for agencies to encourage all providers to be trained in screening procedures so they can recognize early signs and make appropriate referrals, it may be more feasible for EI programs to adopt an implementation model in which certain providers serve as a screening "point-person" and relay the screening results to the family's primary EI provider, who can discuss any concerns with the family.…”
Section: Screening In Ei Programsmentioning
confidence: 99%
“…Survey items were adapted from a prior survey conducted through a CDCAssociation of University Centers on Disabilities Collaboration Research Award (Nalty, 2010) and a prior survey of Illinois service coordinators developed through the Illinois Leadership Education in Neurodevelopmental and Related Disabilities (Pizur-Barnekow, Muusz, Karpinski, O'Connor, & Cutler, 2012). The survey questions were adapted to address the unique roles and perceived preparedness of occupational therapy practitioners in serving young children with special needs and their families.…”
Section: Instrumentmentioning
confidence: 99%